1969
DOI: 10.1111/j.2042-7158.1969.tb08183.x
|View full text |Cite
|
Sign up to set email alerts
|

On the role of a central adrenergic mechanism in morphine analgesic action

Abstract: The influence of drugs interfering with brain monoamine metabolism on morphine analgesia of rats was estimated by the tail pressure method. Central adrenergic stimulation produced by apomorphine, cocaine, pyrogallol or amphetamine led to stereotyped behaviour and elevation of the pain threshold. Lower doses of these drugs potentiated morphine analgesic action. Reserpine, iproniazid and disulfiram weakened morphine analgesic action. α‐Methyldopa increased morphine action and (±)‐tryptophan did not influence it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
14
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 11 publications
4
14
0
Order By: Relevance
“…However, the picture is clouded by conflicting results. For example, enhancement of morphine analgesia has been caused by drugs that increase central DA neuron activity such as amphetamine and apomorphine (Vedernikov and Afrikanov, 1969). Reduction of morphine analgesia has been demonstrated 0300-9564/81/0051/0213/8 02.00 following administration of several drugs, which decrease central DA levels, such as 6-hydroxydopamine (Nakamura et aI, 1973) and alpha-methyl-p-tyrosine (Verri et al, 1968).…”
Section: Introductionmentioning
confidence: 97%
“…However, the picture is clouded by conflicting results. For example, enhancement of morphine analgesia has been caused by drugs that increase central DA neuron activity such as amphetamine and apomorphine (Vedernikov and Afrikanov, 1969). Reduction of morphine analgesia has been demonstrated 0300-9564/81/0051/0213/8 02.00 following administration of several drugs, which decrease central DA levels, such as 6-hydroxydopamine (Nakamura et aI, 1973) and alpha-methyl-p-tyrosine (Verri et al, 1968).…”
Section: Introductionmentioning
confidence: 97%
“…Reserpine, which causes general depletion of biogenic amines, antagonizes the analgesia produced by morphine in the mouse (Sigg, Caprio & Schneider, 1958;Medakovic & Banic, 1964) as does disulphiram (Vedernikov & Afrikanov, 1969), which depletes brain noradrenaline. However, Contreras & Tamayo (1966) demonstrated that dopamine decreased the analgesic activity of morphine in the rat.…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine has been implicated as a hypoalgesic transmitter, but the picture is clouded by conflicting results. Dopaminomimetic drugs, including apomorphine and amphetamine, have been found to enhance the reaction time to painful stimuli, either in naive (1) or in morphine-injected animals (2). On the other hand, evidence has been provided that intracerebroventricular injection of dopamine partially prevents morphine-induced analgesia (3) and that dopamine receptor stimulation reduces while dopamine receptor blockade increases the antinociceptive effects of vaginal stimulation (4).…”
mentioning
confidence: 98%